Russian Queens of Crime Novels and their Gender Stereotypes - Olga Komarova (Nordlit: Tidsskrift i litteratur og kultur, 2005)
Every autumn Muscovites who like books eagerly anticipate the most important event of the year, a great international book market in Moscow where almost every publishing house in the country presents its new offerings. This event represents an occasion to look at and buy new books, and a chance to meet a favourite author and receive an autograph. It is almost certain that the most popular authors will be the well-known women writers of crime stories. While some of the male writers may feel offended, it is a well-known fact that the Russian literature of detection is dominated by women.